1953. Immune responses, viral shedding, and COVID-19 symptom burden from breakthrough SARS-CoV-2 infection in a 2:1 randomized, double-blind, placebo-controlled Phase 3 study of AZD1222 (ChAdOx1 nCoV-19) vaccination. (15th December 2022) - Sobieszczyk, Magdalena E; Falsey, Ann R; Luetkemeyer, Anne F; Paulsen, Grant C; Riddler, Sharon A; Robb, Merlin L; Rolle, Charlotte-Paige M; Sha, Beverly E; Tong, Tina; Ahani, Bahar; Aksyuk, Anastasia A; Bansal, Himanshu; et al.
Abstract: Background: Breakthrough infections post-COVID-19 vaccination increase with waning immunity and typically produce milder disease than infections in unvaccinated individuals. We investigated immuno-virologic responses and COVID-19 symptom burden upon breakthrough infection in participants from a Phase 3 study of 2-dose primary series AZD1222 vaccination (NCT04516746) to explore disease attenuation. Methods: Study participants who experienced protocol-defined COVID-19 symptoms initiated a series of illness visits over 28 days with collection of sera, nasopharyngeal (NP) swabs and saliva samples (SS), and documentation of symptoms (data-cut off: July 30, 2021). For baseline-seronegative participants with PCR-confirmed SARS-CoV-2 infection ≥15 days after dose 2 of AZD1222 or placebo we assessed: anti-SARS-CoV-2 spike (S), nucleocapsid (N) and neutralizing antibody (Ab) titers by multiplex immunoassay and SARS-CoV-2 pseudovirus assay in sera; viral load by quantitative RT-PCR in NP swabs; and viral shedding by qualitative and quantitative RT-PCR in SS. Data were stratified by age and SARS-CoV-2 variant, and time since primary series dose 2. Results: Illness Day 1 (ILL-D1) S Ab GMTs in AZD1222 vaccinees were similar to peak GMTs seen 14 days after dose 2 of AZD1222 and were higher vs placebo at all timepoints. The magnitude of S Ab response differed by age: median GMTs were lower at ILL-D1 and higher at ILL-D14 in vaccinees aged ≥65 vs 18–64 years (Fig.1). ILL-D1 overall, SARS-CoV-2 ancestral, alpha, and epsilon variant viral load titers in NP swabs were lower in vaccinees vs placebo (Fig 2). Mean viral load in NP swabs and viral shedding titers in SS were lower in vaccinees vs placebo at all timepoints. Vaccinees reported fewer COVID-19 symptoms than placebo participants, and experienced shorter symptom duration, particularly for fatigue and difficulty breathing. Figure 1. SARS-CoV-2 spike IgG antibody titers upon SARS-CoV-2 infection by participant age in AZD1222 vaccinees and placebo recipients during illness visits Figure 2. Quantification of viral load (nasopharyngeal swabs quantitative viral titer) by SARS-CoV-2 variant at Illness Visit Day 1 Conclusion: Improved S Ab responses, lower viral loads, and reduced symptom burden upon breakthrough infection in vaccinees vs placebo recipients, suggest that robust recall responses to AZD1222 vaccination may attenuate COVID-19 disease severity and duration. These findings alongside data on cellular immune responses to breakthrough infection will inform understanding of protective immunity to SARS-CoV-2 infection. Disclosures: Magdalena E. Sobieszczyk, MD, MPH, Bill and Melinda Gates Foundation: Grant/Research Support|Gilead Sciences: Grant/Research Support|Janssen Global Services, LLC: Grant/Research Support|Merck: Grant/Research Support|National Institute of Allergy and Infectious Diseases (NIAID): Grant/Research Support|National Institutes of Health (NIH): Grant/Research Support|Sanofi Pasteur Inc.: Grant/Research Support Ann R. Falsey, MD, BioFire Diagnostics: Grant/Research Support|Janssen: Grant/Research Support|Merck, Sharp and Dohme: Grant/Research Support|Novavax: Advisor/Consultant|Pfizer: Grant/Research Support Anne F. Luetkemeyer, MD, AstraZeneca: Grant/Research Support|Gilead Sciences: Grant/Research Support Grant C. Paulsen, MD, AstraZeneca: Grant/Research Support|Moderna: Grant/Research Support|Pfizer: Grant/Research Support Sharon A. Riddler, MD, National Institute of Allergy and Infectious Diseases (NIAID): Grant/Research Support|National Institutes of Health (NIH): Grant/Research Support|Novimmune: Advisor/Consultant Merlin L. Robb, MD, Walter Reed Army Institute of Research: Advisor/Consultant Charlotte-Paige M. Rolle, MD, MPH, Gilead Sciences: Board Member|Gilead Sciences: Grant/Research Support|Gilead Sciences: Honoraria|Janssen: Board Member|ViiV Healthcare: Board Member|ViiV Healthcare: Grant/Research Support|ViiV Healthcare: Honoraria|Vindico CME: Honoraria Beverly E. Sha, MD, Gilead Sciences: Grant/Research Support|MATEC: Honoraria|University of Chicago: Grant/Research Support|US Government: Grant/Research Support Bahar Ahani, BSC, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Anastasia A. Aksyuk, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Himanshu Bansal, MS, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Justin A. Green, MD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Brett Jepson, MS, AstraZeneca: Contractor via Cytel Jill Maaske, MD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Kathryn Shoemaker, MS, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Stephanie Sproule, MMath, AstraZeneca: Contractor via Joule/System One Ann Marie Stanley, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Deidre Wilkins, BSC, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Tonya L. Villafana, PhD, MPH, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Elizabeth J. Kelly, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds.